Prognostic significance of systemic immunoinflammatory biomarkers in patients with clear cell renal cell carcinoma: a retrospective multicenter analysis - Chen, Danlei; Zhang, Zhuorui; Dong, Longsheng; Feng, Zhiyuan; Yang, Junfeng (Frontiers in Immunology, 2025)
AimsThis study aims to investigate the associations between blood laboratory findings, systemic immune-inflammatory factors, ISUP grade, and prognostic outcomes in patients diagnosed with clear cell renal cell carcinoma (ccRCC).MethodsData were collected from patients diagnosed with ccRCC at the First People’s Hospital of Yunnan Province and Xiangya Hospital of Central South University between 2010 and 2022, encompassing pertinent pathological and clinical information. We employed ordered logistic regression analysis to establish the ISUP grading model and conducted association analyses to explore the relationship between ISUP classification and the 2-year survival rate.ResultsA total of 1,635 patients were included in the study. Our findings indicate that ISUP grading is significantly correlated with serum albumin levels, blood chloride concentrations, the platelet-to-lymphocyte ratio (PLR), and the systemic inflammation response index (SIRI). The preoperative 2-year survival model demonstrated associations with platelet counts (PLT), albumin levels, blood chloride concentrations, and PLR, AUC (0.776 95%IC 0.710, 0.843). Furthermore, the postoperative 2-year survival model exhibited robust correlations with PLT, albumin levels, blood chloride concentrations, PLR, and ISUP grade, AUC (0.877, 95%IC 0.825, 0.917).ConclusionThis study demonstrated the relationship between systemic immune markers, ISUP classification, and prognosis. It established preoperative models for predicting ISUP classification, as well as models for predicting 2-year survival rates both preoperatively and postoperatively.